2016
DOI: 10.3390/ijerph13121221
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Characteristics and Driving Factors of Provincial Wastewater Discharge in China

Abstract: Based on the increasing pressure on the water environment, this study aims to clarify the overall status of wastewater discharge in China, including the spatio-temporal distribution characteristics of wastewater discharge and its driving factors, so as to provide reference for developing “emission reduction” strategies in China and discuss regional sustainable development and resources environment policies. We utilized the Exploratory Spatial Data Analysis (ESDA) method to analyze the characteristics of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…The success of WWTPs in urban regions has provided abundant engineering skills and administrative experience. However, it cannot be transferred directly into the rural wastewater treatment field [3] due to the characteristics of rural wastewater, including fluctuating quality and quantity [4,5]. An analysis of rural wastewater in China from the perspectives of legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The success of WWTPs in urban regions has provided abundant engineering skills and administrative experience. However, it cannot be transferred directly into the rural wastewater treatment field [3] due to the characteristics of rural wastewater, including fluctuating quality and quantity [4,5]. An analysis of rural wastewater in China from the perspectives of legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the model has higher precision than the support vector machine method and adaptive regression splines method [11]. Chen et al investigated the overall status of wastewater discharge in China to analyze its driving factors [12]. Yin et al developed a neural network model to forecast and analyze urban water-energy demand in China [13].…”
Section: Introductionmentioning
confidence: 99%
“…Urban wastewater discharge is one of the main sources of surface and groundwater pollution in China [ 1 ]. It has exceeded industrial pollution and, since 1998, it has become the largest source of environmental pollution in China [ 2 , 3 ]. With economic development and the intensification of urbanization, the discharge of urban wastewater is increasing year by year.…”
Section: Introductionmentioning
confidence: 99%
“…Most past studies paid attention mainly to the simple description of the spatial variation of urban wastewater treatment efficiency without detailed analysis [ 8 ]. Others studied the spatial variations of wastewater discharge [ 3 ]. However, research that focuses on analyzing the urban wastewater treatment efficiency and its spatial variation in China is lacking.…”
Section: Introductionmentioning
confidence: 99%